The Complicated Relationship between Literature and the Holocaust: A New Anthology Dealing with an Old Problem (KULT_online, 2010)
The anthology Literatur und Holocaust, edited by Gerd Bayer and Rudolf Freiburg, is concerned with a subject that has been explored in depth since the end of WWII and has proven to be of a rather controversial nature. The introduction is of an extraordinary quality not necessarily matched by the following twelve essays; the difficulties inherent to this relationship and its analysis are evident. Nevertheless, the anthology lives up to the editors’ intentions and provides a versatile treatise on literature as a means of representation of the Holocaust and the scientific discussion of it.